2012
DOI: 10.1111/cfs.12055
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening kinship families: scoping the provision of respite care in Australia

Abstract: Kinship care is the fastest growing form of out‐of‐home care in Australia, as it is in many other countries. The Victorian Government's response has been to establish 18 programmes across the state to provide support to kinship families. The scoping project described here, based on interviews with key programme staff, explores the experiences of the new programmes in providing support, specifically respite care, to kinship families. It has produced a picture, based on qualitative and quantitative data, of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…In an Australian study not covered in the reviews, Brennan et al (2013) found that informal social supports around caring grandparents often diminished following their taking on the care of their grandchildren. Borenstein and McNamara (2015), in an Australian study, found that workers had assessed a higher level of need for respite than was reflected in requests for respite from carers, consistent with earlier research cited that kinship carers can be reluctant to seek assistance.…”
Section: Help Seeking Among Kinship Carerssupporting
confidence: 76%
See 1 more Smart Citation
“…In an Australian study not covered in the reviews, Brennan et al (2013) found that informal social supports around caring grandparents often diminished following their taking on the care of their grandchildren. Borenstein and McNamara (2015), in an Australian study, found that workers had assessed a higher level of need for respite than was reflected in requests for respite from carers, consistent with earlier research cited that kinship carers can be reluctant to seek assistance.…”
Section: Help Seeking Among Kinship Carerssupporting
confidence: 76%
“…The network has similarities to the 'network of caregivers' reported by Casey Family Programs in the Northwest Foster Care Alumni study (Pecora et al, 2010). There are indications in the literature that regular respite may be the most supportive form of respite, due to the predictability and consistent relationships involved (Borenstein & McNamara, 2015).…”
Section: Respitementioning
confidence: 99%
“…Given the specificity of placements in the extended family and the potential conflict between the two families previously noted in the literature (Aldgate & McIntosh, ; Brown & Sen, ; Kiraly & Humphreys, , ; Vanschoonlandt et al, ), KFFs should be provided with a different accompaniment that considers the particular context in which these families carry out their mandate. This proposal is even more justified in terms of practices where, per various studies (Borenstein & McNamara, ; Liao & White, ; Sakai, Lin, & Flores, ), KFFs are generally less informed about existing services and less inclined to seek support from child welfare services.…”
Section: Discussion and Implications For Practicementioning
confidence: 99%
“…Informal kinship care is common practice, which has made the attainment of statistical data challenging (Gibson & Singh, 2010;Selwyn & Nandy, 2014). The statistical data available for countries such as Australia, the United Kingdom and the United States of America, confirm an increase in formal kinship care (Borenstein & McNamara, 2012;Gibson & Singh, 2010;Selwyn & Nandy, 2014). In Australia, it is estimated that the incidence of informal kinship care is four times greater than that of formal kinship care (Borenstein & McNamara, 2012).…”
Section: Prevalence Of Kinship Carementioning
confidence: 99%
“…The statistical data available for countries such as Australia, the United Kingdom and the United States of America, confirm an increase in formal kinship care (Borenstein & McNamara, 2012;Gibson & Singh, 2010;Selwyn & Nandy, 2014). In Australia, it is estimated that the incidence of informal kinship care is four times greater than that of formal kinship care (Borenstein & McNamara, 2012). In the United States of America, it is estimated to be six times greater than formal kinship care (Gibson & Singh, 2010).…”
Section: Prevalence Of Kinship Carementioning
confidence: 99%